Frequency of Distribution and Relationship of Nail Changes and Oral Mucosal Involvement in Classical Lichen Planus (LP) - Nadia Waqas , Muhammad Amer Saleem , Mahvish Aftab Khan, Nadia Waqas , Muhammad Amer Saleem , Mahvish Aftab Khan (Journal of Rawalpindi Medical College, 2020)
Introduction: LP is an itchy dermatosis. It is of different types with classical LP being a common type. It most commonly affects the skin of the limbs, however, it can affect the mucous membranes, genitals and nails as well. Materials and Methods: 100 patients of classical LP presenting in Dermatology OPD of Benazir Bhutto Hospital were enrolled to assess the involvement of nails and oral mucosa in the disease. Statistical Analysis was done using SPSS version 23. Results: Out of 100 patients, 70% were free from any oral mucosal or nail involvement, whereas, 7% had both oral mucosal as well as nail involvement with classical LP. 18% had oral mucosa affected but nails spared and only 5% had nails affected without oral mucous membrane involvement with the diseases. 25% had oral mucosal involvement with reticular pattern being most common type and 12% showed nail changes with longitudinal ridging being the most common. Fisher’s exact test computed a two tailed p value of 0.0093 showing a significant association of nail changes in classical LP with oral mucosal involvement. Conclusion: Classical LP is an itchy condition which most commonly affects the skin, mucous membranes and nails. However, if oral mucous membranes are involved, the risk of having nails affected by the disease is quite significant. The distribution frequency of nail and oral mucosal changes as well as their predominant subtypes associated with classical LP in South Asians is comparable with rest of the world & other types of LP